Tau-PET imaging with [18F]AV-1451 in Primary Progressive Apraxia of Speech - Utianski, Rene L. (Cortex, 2018)
Apraxia of speech is a motor speech disorder characterized by combinations of slow speaking rate, abnormal prosody, distorted sound substitutions, and trial-and-error articulatory movements. Apraxia of speech is due to abnormal planning and/or programming of speech production. It is referred to as primary progressive apraxia of speech (PPAOS) when it is the only symptom of a neurodegenerative condition. Past reports suggest an association of PPAOS with primary 4-repeat (4R) tau (e.g. progressive supranuclear palsy, corticobasal degeneration), rather than amyloid, pathology. The goal of the current study was to investigate the distribution of tau tracer uptake using [18F]AV-1451 positron emission tomography (PET) imaging in patients with PPAOS. Fourteen PPAOS patients underwent [18F]AV-1451 PET (tau-PET) imaging, [C11] Pittsburgh Compound B (PiB) PET and structural MRI and were matched 3:1 by age and sex to 42 cognitively normal controls. Tau-PET uptake was assessed at the region-of-interest (ROI) level and at the voxel-level. The PPAOS group (n=14) showed increased tau-PET uptake in the precentral gyrus, supplementary motor area and Broca’s area compared to controls. To examine whether tau deposition in Broca’s area was related to the presence of aphasia, we examined a subgroup of the PPAOS patients who had predominant apraxia of speech, with concomitant aphasia (PPAOSa; n = 7). The PPAOSa patients showed tau-PET uptake in the same regions as the whole group. However, the remaining seven patients who did not have aphasia showed uptake only in superior premotor and precentral cortices, with no uptake observed in Broca’s area. This cross-sectional study demonstrates that elevated tau tracer uptake is observed using [18F]AV-1451 in PPAOS. Further, it appears that [18F]AV-1451 is sensitive to the regional distribution of tau deposition in different stages of PPAOS, given the relationship between tau signal in Broca’s area and the presence of aphasia.